(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: About ten to fifteen percent of pregnancies result in premature Preterm Rupture of Membranes (PROM) which is responsible for one-third of preterm deliveries. A membrane’s spontaneous rupture before the commencement of active labour is known as a Pre-labour Rupture of Membrane (PROM). About 70% of PROM occurrences happen during term pregnancies. Our main goal was to determine the maternal and newborn outcomes in PROM instances involving mother and child. Materials and methods: This cross-sectional study was conducted in the Department of Obstetrics and Gynaecology, Marine City Medical College and Hospital, Chattogram, between September 2024 and February 2025. About 104 women with PROM with more than 32 weeks of gestational age who were admitted to the above department for delivery were enrolled in this study. Results: The participants’ age ranged between 18-42 years. Overall, the median age of the respondents was 26 years (Interquartile range [IQR] 22, 28). Mean± SD – 25.49± 4.76 years. The maximum (40) participants were within the age group 23- 27. Patientsaccording to the incidence of parity,reveal the highest number (50) of participants belong to the 2nd gravida. Most participants (38) in this study had achieved a secondary school certificate. Whereas, maximum patients (42.31%) didn’t go for an Antenatal Checkup (ANC) although 27.88% of patients had a previous history of abortion, 16.35% had pre-existing hypertensive disorder and 10.58% had gestational HTN in pregnancy, 20.19% of the patients had pre-existing DM and 8.65% had GDM. 15.38% of patients had a history of PROM in a previous pregnancy. The PROM detection only by clinical assessment was a maximum of 73.08% and with the help of USG, along with clinical assessment was 26.92%. 62.5% of deliveries were made within 24 hours of detection. 81.73% of participants were given birth of their baby by spontaneous delivery, the mode of delivery was 56.73% for vaginal delivery and 43.27% for caesarian section. Most of the causes of the caesarian section were fetal distress (26.67%). Only 33.73% of pregnancies with PROM showed signs of infection and the majority (39.39%) were wound infections. Conclusion: 81.73% of mother were given birth of their baby by spontaneous delivery, the mode of delivery was 56.73% for vaginal delivery and 43.27% for caesarian section. Most of the causes of caesarian section were fetal distress (26.67%). Only 33.73% of pregnancies with PROM showed signs of infection and the majority (39.39%) were wound infections. Foetal outcomes revealed 59.62% of neonates scored 7-9 Apgar score at 1 minute and 64.42% scored 8-10 at 5 minutes. 44.23% of neonates needed admission to NICU and the highest neonatal complication was Neonatal Respiratory Distress Syndrome, which was experienced by 24.04% of neonates, 11.54% experienced neonatal jaundice and 8.54% developed neonatal sepsis. Chatt Maa Shi Hosp Med Coll J; Vol.25 (1); January 2026; Page 17-24